Variation of Beach Profile Along Pahang Coast in Malaysia - Amri Mohd, Fazly; Nizam Abdul Maulud, Khairul; Ara Begum, Rawshan; A. Karim, Othman; Firoz Khan, Md; Norsakinah Selamat, Siti; Aziz Ab Rahman, Abdul; Aizat Saiful Bahri, Mohd; Mastura Syed Abdullah, Sharifah; Khairul Amri Kamarudin, Mohd; Barzani Gasim, Muhammad; Juahir, Hafizan (International Journal of Engineering and Technology, 2018)
Pahang is placed at the east coast of Peninsular Malaysia and has a lot of attractive coasts with interesting scenery, which can capture the attention of people to the coasts. The seven (7) of significant coasts namely Pantai Cherating, Holiday Villa beach, Pantai Balok, Sungai Ular, Pantai Sepat, Pantai Cheruk Palok and Pantai Tanjung Agas are classified has experienced about erosion coastal problem especially having significantly for social, environment and economic value recreational activities along of this shoreline. Coastal erosion is recognized as the permanent loss of land and habitats along of the coast. The variation of beach profile characteristics along the shoreline of Pahang will be identified and described using the beach profile survey and interpolation technique. From that, the information of erosion and accretion for topography surface of coastal was generated by calculating distance and elevation of coasts. Most of these study are consist the sandy coastal. Hence the ranges value of coastal width for Tanjung Agas is shows high value of erosion and accretion with -7.74 and 3.93 m/year. To sum up, the findings of study might be useful in significant decision making for protecting and mitigation measures towards sustainable coastal management along the Pahang coastal.Â